STUDENTS’ CRITICAL THINKING UNDER THREE MODELS OF TEACHING - Nurnia Nurnia; Jafar Ahir; La Ode Muharam; Alberth Alberth (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
The advancement of digital technology has evoked a new teaching paradigm and the incorporation of such technology into models of teaching has been highly appreciated in order to achieve certain learning goals such as students’ critical thinking. This study investigates and examines the difference in critical thinking skills of students taught through the flipped classroom, pure online and direct instruction models. The method of the study is quasi-experiment implemented to students of English majors of Halu Oleo University. A total of 96 students participated as samples sitting in three different classes. Each class was attended by an equal number of 32 samples. Data were collected by giving samples a critical thinking skills test after the model implementation. The data were analyzed by means of two-way analysis of variance. Results of the study show that there is a significant difference of students’ critical thinking skills after the implementation of the three models of teaching and the students from the flipped classroom is observed to have higher critical thinking skills. Keywords: flipped classroom, direct instruction, critical thinking skills